Cultural Perceptions Towards HIV/ AIDS in Southern Ijaw Local Government Area, Bayelsa State, Nigeria - Ebgeripou Annie; Odubo Tonbra Robert (International Journal of Humanities, Education, and Social Sciences, 2026)
Cultural beliefs remain a significant factor shaping public understanding, communication, and health-seeking behaviour related to HIV/AIDS in many communities. This study investigated cultural perceptions of HIV/AIDS in Southern Ijaw Local Government Area, Bayelsa State, Nigeria. A mixed-methods cross-sectional survey design was adopted, involving 400 respondents for the quantitative component and 30 participants for the qualitative interviews. Quantitative data were analysed using SPSS version 26, while qualitative data were analysed thematically. The findings revealed that cultural beliefs and norms strongly influenced respondents’ perceptions, discussions, and health-seeking behaviours related to HIV/AIDS. The study also found that HIV/AIDS was sometimes interpreted through spiritual or moral lenses, which contributed to silence, stigma, and limited open dialogue about sexual health and HIV prevention. The study concludes that cultural perceptions play a critical role in shaping HIV/AIDS awareness and prevention practices in Southern Ijaw. It recommends that parents and caregivers, with support from family welfare units and social workers, should be engaged through community sensitisation and capacity-building programmes to strengthen effective communication about HIV/AIDS and sexuality. Traditional leaders should also be involved in challenging harmful traditional beliefs, reducing HIV-related stigma, and promoting open community dialogue on sexual health. This study contributes to public health and social work practice by highlighting the need for culturally responsive HIV/AIDS education and prevention strategies that engage families, community institutions, and traditional leadership structures.